A comparative study of Dynamic Hip Screw and Proximal Femoral Nail in the management of Intertrochanteric Fractures of the Femur - Gurung, Sandeep; DC, Gopalsagar (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Intertrochanteric fractures account for approximately half of the hip fractures in the elderly because of the osteoporotic nature of the bone. There are various modalities to treat these fractures. The objective of this study was to compare and evaluate the clinical and radiological outcome of intertrochanteric femur fracture treated with Dynamic hip screw (DHS) and proximal femoral nail (PFN). Methods: This study was conducted at Nepalgunj medical college, Department of orthopedics Nepalgunj over a time span of two years. A total of 52 patients were included and randomized into Dynamic hip screw (n=26) and Proximal femoral nail (n=26) group. Patient’s demographic details, perioperative findings, radiological findings and follow up findings were recorded. The results were evaluated and compared. Results: The mean age in our study was 57.63 years. Trivial fall was the most common mode of injury. There was significantly higher intraoperative blood loss in the DHS group. Radiological union and functional outcomes were similar overall, but in case of unstable fracture functional outcome was clinically better in PFN group. Conclusion: From our study we concluded that PFN has better outcome in case of unstable intertrochanteric fractures, however in stable fracture also it has distinct advantage over DHS.